ANALISIS EFEKTIVITAS IMPLEMENTASI KEBIJAKAN UNIVERSAL HEALTH COVERAGE DI INDONESIA TINJAUAN KETERSEDIAAN DAN KUALITAS LAYANAN KESEHATAN : LITERATURE REVIEW - Endah Pravita Putri Aldia Pratama; Safinah Annajah; Khansa Adristi; Novita Dwi Istanti (Jurnal Medika Husada, 2023)
WHO established Universal Health Coverage as an important issue for all countries that aims to protect public budgeting for the provision of quality, equitable, and affordable health services. This research uses the literature review method through search engines such as google scholar. Based on the results of the study, the implementation of the Universal Health Coverage program in Indonesia is still not effective in several health services. This happens because there are several obstacles in the quantity of human resources, factors of public demand that have not been fully met, handling patients in terms of administration, communication and public knowledge and awareness.